Dollarization in East Africa: Causes, Consequences, and Future Forecasts - Musse, Osman Sayid Hassan; Echchabi, Abdelghani (Binus Business Review, 2017)
The dollarization phenomenon has been widespread among the East African countries for many decades. This trend results in several consequences that might be either beneficial or harmful to these countries and their likes.The objective of this research was to empirically examine the causes, consequences and the future scenarios of dollarization in one of the leading regional countries such as Somalia. The research used a survey of over 100respondents and applied descriptive statistics and t-tests to achieve the above objectives. The findings show that the main causes of Dollarization in Somalia are the implementation of the Hawallah (money transfer) system,the remarkable absence of the central bank and other monitoring financial authorities, the increasing exports and imports of the Somalian economy, the loss of confidence in the local Somalian Shilling, and the relative ease atwhich the Somalian Shilling can be printed and manipulated by selected market players. These causes are found to be mainly triggered by the revenue from exports, the policies and regulations implemented by the Somali government, the Somali Diaspora, and the international aid organizations. This has resulted in the foreign traders buying Somali goods at a relatively lower price and taking advantage of the depreciated Somali Shilling against most international currencies.